Key future research questions on mediators and moderators of behaviour change processes for substance abuse - Rehm, Jürgen (Int J Methods Psychiatr Res, 2008)
In summarizing the key themes and results of the second meeting of the German Addiction Research Network ‘Understanding Addiction: Mediators and Moderators of Behaviour Change Process’, the following concrete steps forward were laid out to improve knowledge. The steps included pleas to (1) redefine substance abuse disorders, especially redefine the concept of abuse and harmful use; (2) increase the use of longitudinal and life‐course studies with more adequate statistical methods such as latent growth modelling; (3) empirically test more specific and theoretically derived common factors and mechanisms of behavioural change processes; (4) better exploit cross‐regional and cross‐cultural differences. Funding agencies are urged to support these developments by specifically supporting interdisciplinary research along the lines specified above. This may include improved forms of international funding of groups of researchers from different countries, where each national group conducts a specific part of an integrated proposal. Copyright © 2008 John Wiley & Sons, Ltd.